Pd-Catalyzed Rearrangement Reaction of N-Tosylhydrazones Bearing Allyl Ethers Into Trans-Olefin-Substituted Sulfonylhydrazones - Chang, Yaoyao; Fu, Jianfang; Li, Yingxue; Ding, Rongcai; Liu, Yue; Hu, Jinxing (Frontiers in Chemistry, 2021)
A novel and efficient rearrangement of N-tosylhydrazones bearing allyl ethers into trans-olefin-substituted sulfonylhydrazones is proposed. The reaction involves breakage of the C-O bond and formation of the C-N bond. The reaction can be extended to a wide range of substrates, and the target products can be synthesized smoothly, regardless of the presence of electron-donating and electron-withdrawing groups. The proposed strategy is a new direction in the field of rearrangement reactions.